A middle Pleistocene paleosol sequence from Dawson Range, Central Yukon Territory - Jackson, Lionel; Tarnocai, Charles; Mott, Robert (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractFour paleosols were intersected in a core drilled into the colluvial fill of a largely buried meltwater channel that was last active during the youngest of the pre-Reid glaciation (0.99-0.78 Ma) in the Dawson Range, Yukon Territory. The paleosols are classified as Podzols. The sedimentary sequence and paleosols indicate that at least two middle Pleistocene glacial and interglacial periods are represented in the core. The mean annual temperature exceeded 0° C for thousands of years in the upland environment of the Dawson Range at 61° N during these interglacial periods.